Dynamic Prey Predator Model and multiple forms of Harvest of Infected Prey - S. A. Wuhaib; M. H. Mansour (Tikrit Journal of Pure Science, 2019)
In this paper, the dynamic of prey predator model was discussed when the relationship between them is functional response type III. In addition, when prey exposure to the disease as nonlinear function. Also the infected prey exposed to harvest as a nonlinear and as linear function. The bounded and positive solutions, periodic, conditions of equilibrium points and the stability were we discussed Some results were illustrated in numerical simulations, and show we can use the linear function of harvesting to control on the dices.